IMPROVING STUDENTS' SPEAKING SKILLS THROUGH SOCIODRAMATIC PLAY AT THE SECOND GRADE STUDENTS OF SMA NEGERI 2 MAMUJU - Muhammad Ybnu Taufan (Universitas Negeri Makassar, 2020)
This study aims at finding out the effectiveness of sociodramatic play in improving students' speaking skills. This study is quantitative research with Classroom Action Research (CAR) design. Data sources of the study were the second grade students of SMAN 2 Mamuju. The participants were taken through purposive random sampling technique. Data were collected by using observation, test and questionnaire. In this study, post-test was conducted in three cycles. The results of the study show that students had made some progress during the learning process. In pre-test, most of the students were having poor speaking skills with as many as 53% participants were in this category. However, there were significant improvements toward students' speaking skills with no more students with both very poor and poor speaking skills in third cycle. From the result of the test, it can be concluded that sociodramatic play is useful to improve the students' speaking skills. In addition, most of students feel interested in and enjoy the learning process by having sociodramatic play in speaking class.